Attention and Aesthetic Value - Kyndrup, Morten (The Nordic Journal of Aesthetics, 2023)
We are capable of engaging in different kinds of relations with objects and situations we meet. Any relation is, in principle singular and thus einmalig, unique. Still, certain general types of relationality do exist. Relations may be established with focus (“attention”) on usability, truth, ethics, power, authenticity—and of course, on “beauty,” on aesthetic value. This differentiation is an invention of the Modern world and in itself subject to historical change. In terms of “discursive areas” it has been theorized in varying keys—including quite many universalist ones. We are free to choose our modes of attention. Still, institutionalized discourses in practice pre-configure these modes. Especially when it comes to art and Modernity’s “great divide” between poiesis and aesthesis, the conditions for attentional approaches appear largely pre-figured. The article discusses this pre-configuration and the institutionalized “freedoms” of art and its audience, respectively—including current calls to abolish such differentiations and to transgress the discursive boundaries of art.